Designing coupling behaviors using compliant shape optimization. (August 2018) - Ulu, Nurcan Gecer; Coros, Stelian; Kara, Levent Burak
Abstract: A wide set of assembly blocks such as attachments, connectors, joints, and supports rely on the principle of passively coupling two objects using structural compliance. However, only a limited variety of configurations are prevalent in daily use ( e.g. snap fits) due to the challenge of extending the appropriate mechanical behavior to arbitrary object pairs. In this work, we present a method for computationally designing the mechanical coupling behavior between a rigid object and a compliant enclosure based on high-level specifications such as the ease of engagement and disengagement. At the heart of our approach is the use of deformation profiles as the means to describe and optimize physical coupling characteristics. In particular, we introduce a method that maps the shape parameters of the compliant object onto sequentially observed coupling descriptors such as the grip, insertion and removal forces that develop as the rigid object is engaged. Using this formulation, we present a method for optimizing the rest shape of the compliant object to produce the desired coupling behavior. We demonstrate our approach through a variety of designs and validate it with 3D printed physical prototypes. Highlights: Use of deformation profiles to describe/optimize mechanical behavior is shown. A shape optimization method for compliant coupling behavior design is proposed. A practical insertion simulation for computing deformation profiles is presented.